TOMM40‐APOE haplotypes are associated with cognitive decline in non‐demented blacks: Biomarkers (non‐neuroimaging) / Longitudinal change over time. (7th December 2020) - Deters, Kacie D; Mormino, Elizabeth C; Yu, Lei; Lutz, Michael W; Bennett, David A; Barnes, Lisa L
Abstract: Background: The poly‐T alleles at the TOMM40‐'523 locus are in linkage disequilibrium with APOE alleles (E3 and E4). However, the pattern of this association varies across race and may influence cognition over time. Contrary to those who identify as non‐Hispanic White, few studies have investigated the role of APOE‐'523 genotypes in the Black population. Thus, the goal of our study was to investigate the impact of APOE and TOMM40‐'523 haplotypes on cognitive decline in non‐demented non‐Hispanic Black (NHB) participants, and determine whether effects differ from non‐Hispanic White (NHW) participants. Method: Distributions of APOE and TOMM40‐'523 poly‐T alleles were examined across NHB and NHW individuals without dementia at baseline, from three cohort studies of aging and dementia at the Rush Alzheimer's Disease Center. The impact of zero, one, or two copies of the '523‐Short (S) variant (poly‐T alleles<20) within APOE genotype on a composite measure of global cognition and five separate domains (global, episodic memory, episodic memory, semantic memory, visuospatial ability, and perceptual speed) derived from 19 individual tests, was examined with linear‐mixed models. Result: In NHB with E3/E3 (N=294), '523‐S/S was associated with faster decline in global cognition, episodic memory, and visuospatial ability (Global: β=‐0.048, p=0.017; Episodic: β=‐0.05, p=0.031; Visuospatial: β=‐0.037, p=0.034) relative to those who did not have a copy of '523‐S. In contrast, for NHB E4+ (E3/E4 + E4/E4; N=182), '523‐S/S was associated with slower decline in global cognition and visuospatial ability (Global: β=0.047, p=0.042; Visuospatial: β=0.07, p=0.0005) relative to those without '523‐S. Further, results indicated a racial difference in E4+ such that NHB with '523‐S had a slower rate of decline than NHWs with '523‐S. '523‐S/S was not statistically different than one copy of '523‐S in E3/E3 or E4+ analyses. Conclusion: Our findings suggest '523‐S/S has a different effect on cognitive decline among NHB dependent on APOE allele, and that '523 variation may aid in better prediction of early cognitive decline in NHB individuals. Further, racial differences in the effect of E4‐'523‐S may explain prior mixed findings on E4 and decline in this population.